The Implementation of the Peer Teaching Method to Improve Students' Speaking Skills - Desy Susanti (Journal of Practice Learning and Educational Development, 2026)
This study aims to improve students’ speaking skills in the Indonesian language subject through the implementation of the peer teaching method among fourth-grade students at SD Negeri 011 Pulau Rambai. The research method used is Classroom Action Research (CAR), conducted in two cycles. Each cycle consists of planning, action implementation, observation, and reflection. The subjects of this study were 25 fourth-grade students. Data were collected through observation, interviews, and speaking performance tests. The results of the study showed that the application of the peer teaching method increased students’ confidence, participation, and speaking fluency. By the end of the second cycle, 88% of the students achieved a “good” category in speaking skills. Therefore, the peer teaching method is effective in improving the speaking skills of fourth-grade students.